The Migrant Hero: Culture of Migration and its Implication on Mate Selection among Hadiya Society, Southern Ethiopia (Global Journal of Human-Social Science, 2016)
The phenomenon of migration has been indispensable aspect of human histories, cultures and civilizations. In Ethiopia, the post-1991 period witnessed the beginning of new migration to the republic of South Africa in search of greater economic opportunity particularly for unskilled labor. This paper is meant to disclose the developments of the culture of migration and its social and cultural implication, particularly how the culture of migration influence the long standing traditional practice of mate selection among the Hadiya society. A cross sectional study design was employed. In-depth interview, telephone interview, key informant interview and FGDs were data collection tools. The findings of the study revealed that youth migration to the republic of South Africa is bringing a significant and far reaching consequence on the social fabric of Hadiya society specifically on the traditional system of mate selection. In the tradition of Hadiya society, the primary considerations during mate selection were social acceptance on the basis of one's ascribed qualities like lineage membership and higher position in the stratification.
Keywords: culture of migration; mate selection; abduction; Hadiya society; Ethiopia